The Fundamental Problems and Spatial Differences of Air Transport in Eastern Europe - Erdősi, Ferenc (Discussion Papers, 2012)
Transport in Eastern Europe − particularly in Eastern European aviation − is terra incognita for most Hungarian experts. Eastern Europe is not a homogenous area in the field of air transport but rather a mixture of country blocks or even individual countries showing special features inherited from differing ways of historical development. The development process of aviation in Eastern Europe had variable dynamic and static characteristics compared to that of advances economies. In our development programmes, the fulfilment of closing up-objectives can be guaranteed in advance, but the time spans to achieve them are unpredictable. The best results achieved so far have amounted to keeping up for short periods, but after the regime change, the threat of lagging behind was dominant. The three-part paper aims to provide a presentation on the spatial differences emerging in different periods of the evolution of aviation. On the basis of the analysis, the author’s main conclusions are that Eastern European air transport is still lagging behind its economic potential, and per unit traffic volume of airports and the traffic intensity of airlines still show low avionic intensity.